ANALISIS IMPLEMENTASI SISTEM PENGELOLAAN ADMINISTRASI PADA KANTOR KECAMATAN GILIRENG KABUPATEN WAJO - Mastura Karateng; Burhanuddin Burhanuddin (BADAN PENERBIT STIEPARI PRESS, 2023)
In writing this thesis aims to determine the analysis of the administrative management system at the Gilireng District Office, Wajo Regency and to determine the obstacles faced by employees regarding administrative management in providing community services at the Gilireng District Office, Wajo Regency by using a qualitative research type using a descriptive approach method.